Learning Styles and Academic Performance of Intermediate Pupils - Discutido, Ma. April Joyce (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to assess the extent of learning styles of intermediate pupils in Tomas Claudio Colleges during the School Year 2025–2026 and determine their relationship with academic performance. The respondents were the total population of 240 intermediate pupils. They were described in terms of age, sex, sibling position, number of children in the family, monthly family income, parents’ educational attainment, and parents’ occupation. A descriptive survey research design was utilized, employing a questionnaire checklist to measure the extent of learning styles in terms of visual, auditory, and kinesthetic modalities. Documentary analysis was also conducted to determine the pupils’ academic performance based on their first-quarter average grades.Findings revealed that most of the respondents were 9–10 years old, female, first-born, from families with three children, belonging to an income bracket of ₱20,000 and above, with parents who were college graduates and self-employed. The pupils often utilized visual, auditory, and kinesthetic learning styles as perceived by themselves. Results showed that demographic profile variables such as age, sex, sibling position, family size, income, parents’ educational attainment, and occupation were not significant factors influencing learning styles. Furthermore, the academic performance of the pupils was rated as outstanding, with a mean grade of 91.00. However, no significant relationship was found between learning styles and academic performance.Based on the findings, it was concluded that learning styles do not predict academic performance among the respondents. It is recommended that teachers adopt differentiated and multi-sensory instructional strategies, while school administrators provide appropriate training and resources to support varied learning approaches. Pupils are also encouraged to explore diverse learning strategies to enhance their learning experience..
Keywords: Learning Styles, Visual Learning, Auditory Learning, Kinesthetic Learning, Academic Performance, Intermediate Pupils, Descriptive Research